2009
DOI: 10.1128/jvi.00855-09
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Bacteriophage T7 DNA Polymerase of Low Processivity by Suppressor Mutations Affecting Gene 3 Endonuclease

Abstract: The DNA polymerase encoded by gene 5 (gp5) of bacteriophage T7 has low processivity, dissociating after the incorporation of a few nucleotides. Upon binding to its processivity factor, Escherichia coli thioredoxin (Trx), the processivity is increased to approximately 800 nucleotides per binding event. Several interactions between gp5/Trx and DNA are required for processive DNA synthesis. A basic region in T7 DNA polymerase (residues K587, K589, R590, and R591) is located in proximity to the 5 overhang of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…1 B and C). In a previous study, we found that T7 lacking gene 5 cannot grow in cells containing gp5 in which these basic residues were replaced with neutral residues, Asn (16). Despite this detrimental effect on T7 growth, the only defect observed was a threefold decrease in polymerase activity on ssDNA templates and a reduced processivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 B and C). In a previous study, we found that T7 lacking gene 5 cannot grow in cells containing gp5 in which these basic residues were replaced with neutral residues, Asn (16). Despite this detrimental effect on T7 growth, the only defect observed was a threefold decrease in polymerase activity on ssDNA templates and a reduced processivity.…”
mentioning
confidence: 99%
“…Another basic patch (K587, K589, R590, and R591) is located at the front side of gp5 facing its movement direction along the ssDNA template (denoted as front basic patch, Fbp) (16) (Fig. 1 B and C).…”
mentioning
confidence: 99%
“…5B). Interestingly, similar genetically altered gp3 were found to suppress the phenotype arising from an altered T7 DNA polymerase (27). Thus, any abnormal replication structures seem to be targets for gene 3 endonuclease, perhaps providing a check-point for faithful replication.…”
Section: Discussionmentioning
confidence: 98%
“…Phage growth complementation assay was performed as previously described (27). tRNA aminoacylation assay was performed as previously described (31), except that 20 μM RNA from the complex or E. coli total tRNA, 20 μM [ 3 H] leucine or [ 3 H] arginine (15 Ci/mmol), and 2 μM E. coli aminoacyl-tRNA synthetases were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation